Vernacular as anti-empire: Culture 3 - Ivanov, Andrey (project baikal, 2023)
The article reveals the author’s understanding of the vernacular (“architecture without architects” typical for a certain area and local culture) as a manifestation of the cultural mechanism alternative to the imperial-colonial mechanisms of urban development. It is proposed to call this mechanism “Culture 3”. The examples of post-Soviet Armenia show the fundamental differences between the vernacular and “non-vernacular” (classicist, modernist, postmodernist buildings). The article sets a task to reinterpret architectural history in view of decolonial optics.